Threat of Limited Nuclear War. (September 2019) - Hrubec, Marek
The article addresses the contemporary risks of limited nuclear war and its threat for societies. It offers a critical analysis based on the difference between the strategy of a global destructive war following classical application of standard nuclear weapons, on the one hand, and the new political military plan of limited nuclear war, without its global continuation, on the other. First, the article explains the problems connected with the new US strategic documents pursuing limited nuclear war. Second, within this context of the risks of limited nuclear war, it explains conflicts of political (potentially democratic), corporate, and technical military interests in global capitalism which can lead to the limited nuclear war. Third, it concludes by clarifying the historical trajectory of debates concerning the strategies of possible nuclear war, and stresses the current real danger of limited nuclear war and its possible global escalation.